2021
DOI: 10.1142/s0192415x21500191
|View full text |Cite
|
Sign up to set email alerts
|

Research Advances in Protective Effects of Ursolic Acid and Oleanolic Acid Against Gastrointestinal Diseases

Abstract: The intestinal tract plays an essential role in protecting tissues from the invasion of external harmful substances due to impaired barrier function. Furthermore, it participates in immunomodulation by intestinal microorganisms, which is important in health. When the intestinal tract is destroyed, it can lose its protective function, resulting in multiple systemic complications. In severe cases, it may lead to systemic inflammatory response syndrome (SIRS) and multiple organ dysfunction syndrome (MODS). Thus f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 95 publications
1
9
0
Order By: Relevance
“…Also, UA concentration-dependently blocked clonality of SW620 cells (Figure D). In addition, the impact of UA on normal colonic cells was evaluated, showing that treatment with UA at 7.5, 15, and 30 μM for 24 h did not influence the growth of NCM460 cells (Figure E) nor the morphological feature (Figure F), consistent with some reports. ,, …”
Section: Resultssupporting
confidence: 90%
“…Also, UA concentration-dependently blocked clonality of SW620 cells (Figure D). In addition, the impact of UA on normal colonic cells was evaluated, showing that treatment with UA at 7.5, 15, and 30 μM for 24 h did not influence the growth of NCM460 cells (Figure E) nor the morphological feature (Figure F), consistent with some reports. ,, …”
Section: Resultssupporting
confidence: 90%
“…The body's vitamin D level was significantly deficient, and the risk of diffuse muscle pain in the waist, pelvis, and lower limbs was significantly increased [21]. It had been confirmed in foreign studies [22][23][24] that the level of 25 hydroxyvitamin D showed a significant correlation with the dosage of opioids in tumor patients. The low serum magnesium level was also an important reason for the decrease in opioid sensitivity [25].…”
Section: Discussionmentioning
confidence: 90%
“…Author details 1 The First Clinical Medical College, Lanzhou University, No. 199, Donggang Road West, Chengguan District, Lanzhou, Gansu, China.…”
Section: Abbreviationsmentioning
confidence: 99%
“…IRI occurs in various organs and tissues, such as the liver, kidney, brain, heart, lung, retina, and intestine. Intestinal IRI is a major complication of severe trauma, burns, infection, shock, and cardiopulmonary insufficiency [1]. Intestinal IRI damages intestinal epithelial cells (IECs) and causes intestinal Open Access *Correspondence: wanzhh19@lzu.edu.cn; lengyf@lzu.edu.cn barrier dysfunction, allowing bacterial translocation [2].…”
Section: Introductionmentioning
confidence: 99%